Espécies hortícolas alimentares da população caiçara do sertão de ubatumirim, litoral norte de são paulo: manejo e paisagem - Macedo, Gabriela Silva Santa Rosa [UNESP] (2014)
This paper aims to diagnose and analyze the management of food plants resources of traditional agriculture of caiçara community resident in and around the Serra do Mar State Park (PESM) - Picinguaba situated in the state of São Paulo relating them to management and interference in the landscape . To do that, we seek the light of Comprehensive Ethnoecology, through tools of ethnobotany and anthropology, allowing the analysis of the way of life of the people considering the use and occupation as well as the inclusion and importance of food species, cultivated and non-cultivated, day-to-day lives. Field data were obtained through participant observation and the use of questionnaires and structured and semi-structured interviews. We used the geoprocessing in order to obtain a map from landscape units recognized by farmers correlating emic criterion for distinguishing the landscape with phytosociological and diversity aspects. We can conclude that the system of knowledge, beliefs and feelings influence the management of food plants species and landscapes directly affecting the conservation and variability of plant species and landscapes, although there is pressure to substitutions and legal impediments. From the argument that it is possible to co -exist conservation of natural resources in places with traditional communities considering their conservationist way of life, it is expected that this work will bring contributions to public programs and policies to protect the people who have their culture compromised by restrictions in the laws of a Conservation Unit (UC) and to the conservation of targeted food plants of this study